Clandestine Organizations, al Qaeda, and the Paradox of (In)Visibility: A Response to Stohl and Stohl - Schoeneborn, Dennis; Scherer, Andreas Georg (Organization studies, 2012)
In a recent article published in this journal, Stohl and Stohl (2011) examine the phenomenon of clandestine organizations from a communication-centered perspective. The authors draw primarily on the work of the ‘Montreal School’ of organizational communication, which stresses the constitutive role of communication for organizations. In this response, we argue that the Stohls’ paper does not make full use of the paradigmatic turn that the Montreal School offers to organization studies. In our view, the authors overemphasize the role of communication among organizational members in the constitution of organizations. In contrast, we argue that organizations can also be ‘talked into existence’ by the communicative acts of third parties (e.g., the media), a view that is consistent with the Montreal School’s work. Moreover, drawing on the Stohls’ central example of the terrorist organization al Qaeda, we suggest that the attribute ‘clandestine’ does not capture the essence of that organization because it is characterized by extreme invisibility of its governance structures and by extreme visibility of its terrorist activities. We believe it is the reversion of the relation between invisibility and visibility that differentiates al Qaeda from legitimate organizations such as private businesses and ensures its perpetuation against all odds.